Efficacy of Liver Resection for Single Large Hepatocellular Carcinoma in Child-Pugh A Cirrhosis: Analysis of a Nationwide Cancer Registry Database - Hong, Suk Kyun; Lee, Kwang-Woong; Hong, Su young; Suh, Sanggyun; Hong, Kwangpyo; Han, Eui Soo; Lee, Jeong-Moo; Choi, YoungRok; Yi, Nam-Joon; Suh, Kyung-Suk (Frontiers in Oncology, 2021)
Background: Therapeutic strategies and prognostic factors for patients with single large hepatocellular carcinoma (HCC) are needed. This retrospective study aimed to identify the prognostic factors for patients with single large HCC with good performance status and Child-Pugh A cirrhosis using a large national cancer registry database and recommend therapeutic strategies. Methods: Among 12 139 HCC patients registered at the Korean Primary Liver Cancer Registry between 2008 and 2015, single large (≥5 cm) HCC patients with Eastern Cooperative Oncology Group (ECOG) performance status 0 and Child-Pugh score A were selected. Results: Overall, 466 patients were analyzed. The 1-,2-,3-, and 5-year survival rates after initial treatment were 84.9%, 71.0%, 60.1%, and 51.6%, respectively, and progression-free survival rates were 43.6%, 33.0%, 29.0%, and 26.8%, respectively. Platelet count <100 ⅹ 109/L (P <0.001), sodium level <135 mmol/L (P = 0.002), maximum tumor diameter ≥10 cm (P = 0.001), and treatment other than resection (transarterial therapy vs. resection: P <0.001, others vs. resection: P = 0.002) were significantly associated with poorer overall survival; sodium <135 mmol/L (P = 0.015), maximum tumor diameter ≥10 cm (P<0.001), and treatment other than resection (transarterial therapy vs. resection: P<0.001, others vs. resection: P=0.001) were independently associated with poorer progression-free survival. Conclusion: Resection as an initial treatment should be considered when possible, even in patients with single large HCC with good performance status and mild cirrhosis. Caution should be exercised in patients with low platelet level (< 100 × 109/L), low serum sodium level (< 135 mmol/L), and maximum tumor diameter ≥ 10 cm.